“Near-Miss” Obstetric events and maternal mortality in a Tertiary Care Hospital - Shravya Tallapureddy; Revathi Velagaleti; Himabindu Palutla; Chaitanya Venkata Satti (Indian Journal of Public Health, 2017)
Obstetric near-miss or severe acute maternal morbidity is gaining interest internationally as a new indicator of the quality of obstetric care. This is a retrospective study conducted using “The WHO Near-Miss Approach” to provide insight into obstetric emergencies, near-miss cases, and maternal deaths in our hospital. The maternal near-miss ratio was 8.4/1000 live births, maternal near-miss to mortality ratio was 5.3:1. Hemorrhage was the leading cause (43.7%) of morbidity in near-miss cases while hypertensive disorders were the leading cause in maternal deaths (66.6%). Among women with potentially life-threatening conditions, severe preeclampsia was the most common complication (50.54%). The near-miss approach helps to evaluate and improve the quality of care provided by health system by identifying the pattern of severe maternal morbidity and mortality, strengths and weakness in the referral system and the clinical interventions available and the ways in which improvements can be made.